2012
DOI: 10.1016/j.cell.2011.10.048
|View full text |Cite
|
Sign up to set email alerts
|

A Recently Evolved Transcriptional Network Controls Biofilm Development in Candida albicans

Abstract: A biofilm is an organized, resilient group of microbes where individual cells acquire properties, such as drug resistance, that are distinct from those observed in suspension cultures. Here we describe and analyze the transcriptional network controlling biofilm formation in the pathogenic yeast Candida albicans, whose biofilms are a major source of medical device-associated infections. We have combined genetic screens, genome-wide approaches, and two in vivo animal models to describe a master circuit controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,081
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(1,156 citation statements)
references
References 109 publications
40
1,081
4
1
Order By: Relevance
“…6B). To explore the working model of piperazine derivatives on the morphological transition of C. albicans , we continued to test whether these compounds interfered with the signalling pathways of the hyphae development process (Sudbery et al ., 2004; Lu et al ., 2011; Shareck and Belhumeur, 2011; Nobile et al ., 2012). Real‐time PCR analysis showed that exogenous addition of the leading compound 28e inhibited the expression levels of CDC35, EFG1, TEC1 and HWP1, which are regulators involved in the cAMP‐PKA pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6B). To explore the working model of piperazine derivatives on the morphological transition of C. albicans , we continued to test whether these compounds interfered with the signalling pathways of the hyphae development process (Sudbery et al ., 2004; Lu et al ., 2011; Shareck and Belhumeur, 2011; Nobile et al ., 2012). Real‐time PCR analysis showed that exogenous addition of the leading compound 28e inhibited the expression levels of CDC35, EFG1, TEC1 and HWP1, which are regulators involved in the cAMP‐PKA pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ndt80p occupies the promoter region of roughly a quarter of total C. albicans genes under yeast-form growth conditions, suggesting wide functions for Ndt80p [57]. Indeed, it was shown that Ndt80p regulates different processes including drug resistance, cell separation, hyphal differentiation, biofilm formation and virulence [54,57,58]. Importantly, the C. albicans ndt80D/ndt80D mutant is unable to form true hyphae under different filamentation-inducing conditions and, in the presence of serum at 37uC, it fails to activate the expression of HSGs, including HWP1, ECE1, RBT4, ALS3, HYR1 and SAP4 [58], all directly regulated by Sfl2p (Figure 6), as well as the transcription factor-encoding genes TEC1 and UME6 which are both directly modulated by Sfl1p and Sfl2p ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although Efg1p binding is altered upon hyphal induction, Efg1p co-immunoprecipitated with Sfl2p ( Figure 9B) at 37uC in Lee's medium, which may explain Sfl2p dependency on EFG1 to regulate morphogenesis under certain conditions. Nobile et al elegantly showed that an intricate transcriptional network involving Ndt80p, Efg1p, Brg1p, Bcr1p, Rob1p and Tec1p controls biofilm development in C. albicans [54]. Interestingly, with the exception of BCR1, all genes encoding these regulators are direct targets of Sfl1p or Sfl2p ( Figure 6 and [54]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations